Rumors across social platforms from perception of anchors and journalists in the kingdom of Jordan post Covid-19 pandemic - Bani odeh, Ahmed Rasheed (Journal of Humanities & Social Sciences, 2023)
The study was carried out to identify rumors across social platforms from perceptions of anchors and journalists. The study was introduced in several sections, namely, investigate the attitude of Jordanian anchors and journalists toward using social platforms as a source of information and for propagating news, the most spread rumors across social media platform, factors facilitate rumors spreading across social media, and its causes and recoomndation to suppress this phenomenon. The study was descriptive and used an online survey distributed randomly across 320 Jordanian anchors and journalists. The study revealed that 53% of Jordanian journalists use social platforms for posting news and information, and they show a low dependency level on social platforms for information or news. The study also revealed that political rumors are the most propagated rumors across social media. Then, social, political, security, and religious rumors, respectively. The study found that the aim of rumors is audience misleading and serves political purposes in Jordan. The journalists disclosed that Jordanians spread rumors across social media due to their beliefs in citizen journalism and gaining attention and interest. However, the journalists reported the negative attitudes of citizens dealing with rumors because citizens first spread rumors without validating them from reliable resources. Accordingly, anchors and journalists recommend applying the electronic rumors codes.
Keywords: Anchors; Hashemite kingdom of Jordan; journalists; reporters; rumors; social media platforms